A Discussion of the Concept of Spirituality - Delgado, Cheryl (Nursing Science Quarterly, 2005)
The purpose of this article is to discuss the concept of spirituality. There is a recognized connection between spirituality and health, and nurse leaders have acknowledged the importance of the spiritual as well as the physical in providing optimal nursing care. Spirituality goes beyond religious or cultural boundaries. Spirituality is characterized by faith, a search for meaning and purpose in life, a sense of connection with others, and a transcendence of self, resulting in a sense of inner peace and well-being. A strong spiritual connection may improve one’s sense of satisfaction with life or enable accommodation to disability.